2019
DOI: 10.18551/erudio.6-2.7
|View full text |Cite
|
Sign up to set email alerts
|

The Visionary Leadership Strategy in Advancing Educational Institutions

Abstract: Educational institutions need clearer directions for all organization members. Organizations need people to be able to set the direction forward, spread it to all organization members, direct people to achieve goals, build networks with other institutions, provide incentives, motivate, and give awards to outstanding subordinates. People able to do such things are called visionary leaders. Therefore, this study aims to analyze the visionary leadership strategy in advancing educational institutions in order to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The existence of visionary leadership in the process of implementing education management becomes a driving force to produce a process of building a culture of innovation through habituation or habituation and can influence the school's cultural climate to improve the performance of educators and education staff in carrying out their professional duties. The visionary leadership action taken by the principal as the manager is to achieve and realize the quality of future education [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of visionary leadership in the process of implementing education management becomes a driving force to produce a process of building a culture of innovation through habituation or habituation and can influence the school's cultural climate to improve the performance of educators and education staff in carrying out their professional duties. The visionary leadership action taken by the principal as the manager is to achieve and realize the quality of future education [10].…”
Section: Resultsmentioning
confidence: 99%
“…Visionary leadership teaches a culture of performance improvement in welcoming progress with optimism, despite facing tough and severe challenges [10]. Visionary leadership motivates the courage to face risks as a reality that must be resolved and managed optimally, not eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…A leadership approach that focuses on future transformations is known as visionary leadership [64]. In education, the visionary leadership strategy emphasizes interdependence and mutual needs among schools, teachers, and other administrative staff [65]. Visionary leadership also refers to leadership conduct that is focused on future developments through the capacity of leaders to engage in anticipating, innovating, formulating, socializing, and implementing ideas by involving and educating all employees within the organization in order to successfully work on achieving the established goals and objectives [64].…”
Section: Human and Non-human Influenced Constructs In Measuring Digit...mentioning
confidence: 99%
“…This situation necessitates further research to obtain a more comprehensive understanding of this matter. Ubaidillah et al (2019) revealed that visionary leadership is urgent for implementing education to realize institution-advanced education and become the central concern and hope. Leaders see realistic, convince, and guide leadership organizations to reach more future aspirations.…”
Section: Introductionmentioning
confidence: 99%